Speech by the Hon’ble Chief Minister ,Penang at the Launching of Pasar Seni Penang at The Youth Park on 8th. August 1976 at 10.am. - Lim, Chong Eu (1976)
It gives me great pleasure to attend this colourful ceremony to mark the launching of Pasar Seni, Pulau Pinang.This is a project which is organised by the Department of Culture, Youth and Sports in the State of Penang.